2017
DOI: 10.1177/2374373517718146
|View full text |Cite
|
Sign up to set email alerts
|

What’s Mine is Yours

Abstract: This study is a long-term follow-up on the health and quality of life of Good Samaritan living organ donors who donated an average of 10 years ago. Thirteen donors (kidney, liver, and lung) completed 2 surveys. Data from the RAND 36-Item Health Survey showed that for all domains, as well as the physical and mental component summary scales, the Good Samaritan donor outcomes were superior to the general population (P < .0001). Data from the European Living Donor Satisfaction Survey (EULID) showed that in all 8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Finally, while quantitative studies are useful in comparing levels of complaints and well-being to established benchmarks, these figures add little in the way of knowledge on the experience of the anonymous donation process by donors. For this, qualitative research is needed, either in the form of focus groups or interviews (Balliet et al, 2019;Bramstedt, 2018;Maghen et al, 2018). Pertinent questions include the impact of anonymity on mental health after donation as well as the extent to which any psychological problems may be attributed to the donation process and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while quantitative studies are useful in comparing levels of complaints and well-being to established benchmarks, these figures add little in the way of knowledge on the experience of the anonymous donation process by donors. For this, qualitative research is needed, either in the form of focus groups or interviews (Balliet et al, 2019;Bramstedt, 2018;Maghen et al, 2018). Pertinent questions include the impact of anonymity on mental health after donation as well as the extent to which any psychological problems may be attributed to the donation process and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…A large crosssectional study comparing UKDs with specified kidney donors showed no significant difference between groups in current or past psychiatric symptoms and well-being (Maple et al, 2014). Conversely, a retrospective study among thirteen UKDs, 10 years after donation, showed that health-related quality of life among donors was significantly superior to that of the general population (Bramstedt, 2018). Given the paucity in research in this target group, greater understanding of the (long-term) impact of anonymous donation on mental health is needed.…”
Section: Introductionmentioning
confidence: 99%
“…3,17 However, detrimental impact to donors and recipients, when faced with negative outcomes, has also been reported. 3,18 At the University of Toronto, to maintain equivalence with Canada's legal requirements for anonymity with deceased donations and given reported concerns from donors, anonymity on both parties was maintained during the entire donation process. The donors were informed about the immediate posttransplant condition of the recipient.…”
Section: Follow-up and Donor-recipient Contactmentioning
confidence: 99%
“… 3 , 17 However, detrimental impact to donors and recipients, when faced with negative outcomes, has also been reported. 3 , 18 …”
Section: Introductionmentioning
confidence: 99%